A multi-group structural equation modelling analysis for the impact of digital art on critical thinking across language contexts - Gulvira Togabayeva; Rabilova Zoya; Miyat Janayev; Gulnar Shaizadanova; Anarbek Kozybay (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study investigates the structural relationships among creativity (Crtvt), technological adaptability (TchAd), problem solving (PrblS), analytical thinking (Anlyt), and self-reflection (SlfRf) in the context of digital art education. A total of 249 students from three higher education institutions in Kazakhstan participated in the study. Using a 25-item Likert-scale instrument, data were collected from students instructed in either Kazakh or Russian. Structural equation modeling (SEM) with multi-group analysis was employed to test a theoretically grounded model of critical thinking development through digital art. The results revealed that Crtvt and TchAd significantly predicted students’ problem-solving abilities, which in turn emerged as the strongest predictor of both Anlyt and SlfRf. Crtvt also had moderate direct effects on these higher-order thinking outcomes, while TchAd showed a stronger influence on PrblS and SlfRf than on Anlyt. Multi-group analysis indicated that the measurement and structural models were invariant across language groups.